Effects of Cold Water Immersion and Heat Exposure on Post-Exercise Recovery and Training Adaptations: A Narrative Review - Wolff, Magdalena; Sobczak, Agata; Kowalczyk, Maja; Kreft, Kalina; Waldman, Anna; Głuszkiewicz, Lena (Quality in Sport, 2026)
Background: Cold water immersion (CWI) and heat exposure, including hot water immersion (HWI) and sauna bathing, are commonly used to enhance post-exercise recovery. Although both interventions are widely applied in sport, they elicit distinct physiological responses and may differently influence recovery and training adaptations. Aim: This narrative review aimed to summarize current evidence on the effects of CWI and heat exposure on post-exercise recovery and training adaptations, focusing on physiological mechanisms and practical applications. Materials and methods: A narrative review was conducted using publications retrieved from PubMed, Scopus, Web of Science, and Google Scholar. Original studies, randomized controlled trials, systematic reviews, and meta-analyses investigating CWI, HWI, and sauna bathing were included. Priority was given to studies published between 2023 and 2025, with earlier landmark studies providing physiological context. Results: Current evidence indicates that CWI effectively reduces delayed-onset muscle soreness and perceived fatigue, supporting short-term recovery. However, regular post-exercise use after resistance training may attenuate hypertrophic adaptations by suppressing anabolic signaling. In contrast, HWI and sauna bathing promote thermoregulatory adaptations, increase plasma volume, and improve heat tolerance, although evidence for post-exercise recovery remains limited. Their effectiveness depends on training goals, exercise modality, timing, and treatment protocol. Conclusions: Cold and heat exposure should be regarded as complementary rather than competing recovery strategies. CWI is primarily supported for short-term recovery, whereas HWI appears most beneficial for enhancing thermoregulatory adaptations and preparation for exercise in hot environments. Thermal therapies should be individualized according to the athlete's training goals and training phase.